PP.33.12: SIMILAR ADIPONECTIN CONCENTRATIONS IN OBESE NORMOTENSIVE AND OBESE HYPERTENSIVE MEN AND NO VASORELAXANT EFFECT OF ADIPONECTIN ON HUMAN ARTERIES. (June 2015) - Dreier, R.; Asferg, C.; Derg, J.; Flyvbjerg, A.; Frystyk, J.; Linneberg, A.; Jeppesen, J.; Edvinsson, L.; Skovsted, G.
Abstract : Objective: Obesity is a strong risk factor for hypertension but the mechanism linking obesity to hypertension is not fully elucidated. In obesity, circulating concentrations of adiponectin are decreased and hypoadiponectinamia has in some but not all studies been associated with increased risk of hypertension. Due to this inconsistency, we decided to study adiponectin from 2 aspects in a cross-sectional in vivo study and in an experimental in vitro study. Design and method: In the cross-sectional study, 103 men with body mass index (BMI) >  = 30.0 kg/m2 were studied; 63 had 24-hr ambulatory blood pressure (AMBP) >  = 130/80 mmHg (OHT) and 40 had 24-hr AMBP < 130/80 mmHg (ONT). As controls, we studied 27 men with BMI between 20.0 and 24.9 kg/m2 and 24-hr AMBP < 130/80 mmHg (LNT). Serum concentrations of adiponectin and body composition using dual energy X-ray absorptiometry scanning were determined. In the in vitro study, the direct vasomotor response of adiponectin was tested on subcutaneous resistance arteries from human abdominal adipose tissue. Results: The 2 obese groups had lower serum adiponectin concentrations compared with LNT (P < 0.01) (median (interquartile range): OHT 6.5 (5.1–8.3) mg/L; ONT 6.6 (5.2–7.8) mg/L; and LNT 9.4 (6.7–12.4) mg/L, but there was no significant difference in adiponectin concentrations (or body composition) between OHT and ONT (P = 0.67), although OHT had much higher 24-hr systolic AMBP (mean ± SD: 137 ± 11 mm Hg vs. 117 ± 6 mm Hg, P < 0.001) and much higher 24-hr diastolic AMBP (mean ± SD: 83 ± 6 mm Hg vs. 73 ± 4 mm Hg, P < 0.001) compared with ONT. In the in vitro study, adiponectin neither had any direct vasodilatory effect nor did adiponectin affect angiotensin II stimulated vasoconstriction. Conclusions: Despite large differences in 24-hr AMBP (and comparable body compostion), obese hypertensive men had similar serum concentrations of adiponectin as obese normotensive men, and furthermore adiponectin did not show any vasodilatory properties in human subcutaneous resistance arteries. Thus overall, our findings do not support a major role, if any, for adiponectin in human hypertension.